Potential value and research frontiers of viruses in inflammatory bowel diseases: a bibliometric analysis - Zhang, Wei; Zou, Menglong; Zhou, Yao; Tang, Qiwei; Zhu, Ying; Xu, Yin (Frontiers in Microbiology, 2025)
BackgroundThe pathogenesis of inflammatory bowel diseases (IBD) and their interaction with viruses have attracted growing scientific attention, as viral infections and gut virome dysregulation are increasingly recognized as key drivers of IBD onset, disease activity, and treatment responses. However, a systematic analysis of research trends in this field is lacking, leaving critical gaps in understanding how viral factors shape IBD pathogenesis and clinical management. This study conducted a bibliometric analysis to map trends, key areas, and emerging topics in the virus-IBD field from 2014 to 2024, with a focus on the pathogenic roles of viruses. The goal was to inform future research directions and bridge the gap between basic science and clinical practice.MethodsPublications related to virus-IBD were retrieved from the Web of Science Core Collection. The analysis employed VOSviewer, CiteSpace, and HistCite software to explore bibliometric dimensions, including annual publication trends, contributions by countries/regions and institutions, collaboration networks, highly cited references, citation bursts, and keyword co-occurrence and evolution.ResultsAmong 3,225 publications analyzed, three distinct phases were observed: fluctuating growth (2014–2019), a sharp rise (2020–2021), and a gradual decline (2022–2024). The United States (996 publications) and China (507 publications) were the dominant contributors to the field. The Mayo Clinic led in institutional publication output, while Jean-Frederic Colombel and Silvio Danese were among the most prolific and cited authors. Inflammatory Bowel Diseases and Frontiers in Immunology were leading journals. Keyword and reference analyses highlighted major research domains: gut virome mechanisms and modulation, clinical strategies for opportunistic viral infections, and IBD management during Coronavirus Disease 2019 (COVID-19).ConclusionThis study establishes an integrated knowledge framework of virus-IBD research, highlighting three essential domains: gut virome regulation and therapy, clinical management of opportunistic viral infections, and IBD care in the COVID-19 era. It further clarified the pathophysiological interplay between viral factors and IBD. By synthesizing key contributors, core themes, and evolutionary trends, this work provides a practical foundation for guiding translational research and promoting clinical innovation.